Peningkatan Minat Belajar Matematika Melalui Strategi Pembelajaran Kooperatif Tipe Jigsaw Pada Siswa Kelas Xi Semester Genap Smk N 1 Banyudono Tahun Ajaran 2015/ 2016 - Widi Yunitasari, Utika (2016)
The purpose of this research is to increase the interest study for the student in the mathematics lesson using cooperative learning strategy type Jigsaw by this many indicator: a) enthusiastic in the learning activity, b) ask about the material which no clear, and c) take participate in the team learning. This research subject is Endang Dwiyani, S.Pd as mathematic teacher in XI AK 1 SMK N 1 Bayudono as subject who give action, school head SMK N 1 Bayudono as subject who help in accumulation data, meanwhil the student XI AK 1 SMK N 1 Bayudono teaching year 2015/ 2016 who aggregate 36 woman as subject researcher who accept action. Methode accumulation data in this research is observation, field note and documentation. The data analysis from three step consist of data reduction, data presentation, and pulling conclusion. This research product is a) increasing the student enthusiastic in the learning activity from 27,78% to be 60%, b) increasing quantity student ask about the material which not clear from 8,33% to be 42,86%, and c) increasing take participate student in the team learning from 19,44% to be 54,28%.